2017
DOI: 10.4049/jimmunol.1601687
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Pathogenic Cellular Networks by IL-21 Blockade Leads to Disease Amelioration in Murine Lupus

Abstract: Systemic lupus erythematosus (SLE, lupus) is characterized by autoantibody-mediated organ injury. Follicular helper T cells (Tfh) orchestrate physiological germinal center (GC) B cell responses, while in lupus they promote aberrant GC responses with autoreactive memory B cell development and plasma cell-derived autoantibody production. IL-21, a Tfh cell-derived cytokine, provides instructional cues for GC B cell maturation, with disruption of IL-21 signaling representing a potential therapeutic strategy for au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 55 publications
1
39
0
Order By: Relevance
“…Cytometric, transcriptomic, and functional analyses presented here indicate that the PD-1 hi CXCR5 -Tph cell population shows a strong resemblance to Tfh cells, including expression of IL-21 and CXCL13 ex vivo, consistent with prior observations of Tph cells in rheumatoid synovium (22). Given the key roles of IL-21 in autoreactive B cell activation, autoantibody production, and renal injury in murine models of lupus, we hypothesize that IL-21 production is an important aspect of Tph cell function, although other pathologic roles independent of B cell-helper function are also possible (43,44). Subsequent studies will help to define the relationship between PD-1 hi and PD-1 + T cells and the relationship between Tph cells and Tfh cells in SLE patients.…”
Section: Discussionsupporting
confidence: 87%
“…Cytometric, transcriptomic, and functional analyses presented here indicate that the PD-1 hi CXCR5 -Tph cell population shows a strong resemblance to Tfh cells, including expression of IL-21 and CXCL13 ex vivo, consistent with prior observations of Tph cells in rheumatoid synovium (22). Given the key roles of IL-21 in autoreactive B cell activation, autoantibody production, and renal injury in murine models of lupus, we hypothesize that IL-21 production is an important aspect of Tph cell function, although other pathologic roles independent of B cell-helper function are also possible (43,44). Subsequent studies will help to define the relationship between PD-1 hi and PD-1 + T cells and the relationship between Tph cells and Tfh cells in SLE patients.…”
Section: Discussionsupporting
confidence: 87%
“…Lpr model (58), anti-IL-21R mAb treatment in the NZB/W F1 model (59), and anti-IL-21 mAb treatment in the B6.Sle.Yaa model (60).…”
Section: Il-21r-fc Treatment In the Mrl-fasmentioning
confidence: 99%
“…6 Inhibition of these signals by blocking antibodies results in loss of both GC Tfh and GC B cells. [41][42][43][44] After antigen clearance, GCs resolve and long- 49 and consequently, alterations in miRNA expression have been associated with several human diseases, such as cancer and autoimmunity. [49][50][51] Recent work also demonstrated that miRNAs serve as critical regulators of the immune system in a variety of cell types by directing lineage commitment, proliferation, differentiation, and migration.…”
Section: Gcmentioning
confidence: 99%